A dinâmica e o funcionamento da cadeia global de valor da indústria automobilística na economia mundial - Uallace Moreira Lima (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The new strategies of internationalization of production lie in the fact many industries leave the condition of bounded entities nationally for the condition of fragmented business networks, in organizational terms, globally distributed, leading companies to engage in the production of a good or service, from conception to consumption. This new strategy, which gains strength mainly from the 1990s to the productive globalization, is best known as Global Value Chains (GVCs). The global automotive industry, like many others, is in the midst of this profound transition. Since the mid-1980s, there is a transition from national industries located in a limited number of countries for a more integrated global industry. Factors such as market saturation, high levels of motorization and political pressure on automakers to produce where they sell have encouraged the dispersion of final assembly, making the production happen in many more places than thirty years ago. Therefore, the aim of this paper is to analyze the functioning of the global value chain of the automotive industry, its dynamics and trends, taking into account the organization of the production process in the world economy and its foreign trade.
Keywords: F02; L62; L00; L2; O3; 330; global value chains; automobile industry; follow sourcing